Emergence of the Epidemic Methicillin-Resistant Staphylococcus aureus Strain USA300 Coincides with Horizontal Transfer of the Arginine Catabolic Mobile Element and speG-mediated Adaptations for Survival on Skin. - GEOGHEGAN, JOAN (My University, 2013)
The arginine catabolic mobile element (ACME) is the largest genomic region distinguishing epidemic USA300 strains of methicillin-resistant Staphylococcus aureus (MRSA) from other S. aureus strains. However, the functional relevance of ACME to infection and disease has remained unclear. Using phylogenetic analysis, we have shown that the modular segments of ACME were assembled into a single genetic locus in Staphylococcus epidermidis and then horizontally transferred to the common ancestor of USA300 strains in an extremely recent event. Acquisition of one ACME gene, speG, allowed USA300 strains to withstand levels of polyamines (e.g., spermidine) produced in skin that are toxic to other closely related S. aureus strains. speG-mediated polyamine tolerance also enhanced biofilm formation, adherence to fibrinogen/fibronectin, and resistance to antibiotic and keratinocyte-mediated killing. We suggest that these properties gave USA300 a major selective advantage during skin infection and colonization, contributing to the extraordinary evolutionary success of this clone.
PUBLISHED
Keywords: Staphylococcus aureus